Postoperative systemic inflammatory dysregulation and corticosteroids: a narrative review. (29th October 2022) - Bain, C. R.; Myles, P. S.; Corcoran, T.; Dieleman, J. M.
Summary: In some patients, the inflammatory‐immune response to surgical injury progresses to a harmful, dysregulated state. We posit that postoperative systemic inflammatory dysregulation forms part of a pathophysiological response to surgical injury that places patients at increased risk of complications and subsequently prolongs hospital stay. In this narrative review, we have outlined the evolution, measurement and prediction of postoperative systemic inflammatory dysregulation, distinguishing it from a healthy and self‐limiting host response. We reviewed the actions of glucocorticoids and the potential for heterogeneous responses to peri‐operative corticosteroid supplementation. We have then appraised the evidence highlighting the safety of corticosteroid supplementation, and the potential benefits of high/repeated doses to reduce the risks of major complications and death. Finally, we addressed how clinical trials in the future should target patients at higher risk of peri‐operative inflammatory complications, whereby corticosteroid regimes should be tailored to modify not only the a priori risk, but also further adjusted in response to markers of an evolving pathophysiological response.